Modelling human Puumala hantavirus infection in relation to bank vole abundance and masting intensity in the Netherlands. Issue 1 (1st January 2017) - Swart, Arno; Bekker, Dick L.; Maas, Miriam; de Vries, Ankje; Pijnacker, Roan; Reusken, Chantal B. E. M.; van der Giessen, Joke W. B.
ABSTRACT: This paper deals with modelling the relationship between human Puumala hantavirus (PUUV) infection, the abundance and prevalence of infection of the host (the bank vole), mast, and temperature. These data were used to build and parametrise generalised regression models, and parametrise them using datasets on these factors pertaining to the Netherlands. The performance of the models was assessed by considering their predictive power. Models including mast and monthly temperature performed well, and showed that mast intensity influences vole abundance and hence human exposure for the following year. Thus, the model can aid in forecasting of human illness cases, since (1) mast intensity influences the vole abundance and hence human exposure for the following year and (2) monitoring of mast is much more feasible than determining bank vole abundance.